Upregulated Expression of SHMT2 Predicts Poor Survival of Lung Adenocarcinoma - Qi Guo; Guang-Hong Huang; Pu Chen; Chao Guo (Genetics Research)
Conclusions: Our research indicated that elevated SHMT2 expression is strongly linked to adverse clinical characteristics and poor prognosis in LUAD patients. Consequently, SHMT2 may represent a novel prognosis marker and a promising therapeutic target regarding the treatment of LUAD.